ANALISIS OF THE PROBLEM OF AEROSPASE INDUSTRI IMPACT ON THE ENVIRONMENT - Vasiljeva, Irina (Proceedings of National Aviation University (archive), 2006)
The article describes the major industrial processes within the aerospace industry, including the materials and equipment used, and the processes employed.